Long-term cognitive and behavioral outcomes following early exposure to general anesthetics. Issue 4 (5th August 2022) - Ing, Caleb; Bellinger, David C.
Abstract : Purpose of review: Nearly 100 clinical studies have been published evaluating neurodevelopmental outcomes in children following surgery and anesthesia. These studies have reported mixed results, likely attributable at least in part to significant heterogeneity in their study designs, types and numbers of exposures, patient populations evaluated, and most importantly, the outcomes that were assessed. This review aims to summarize the results from clinical studies evaluating behavioral outcomes in children exposed to surgery and anesthesia. Recent findings: Children with early exposure to surgery and anesthesia were found to have limited to no differences in intelligence when compared with unexposed children. However, several studies have reported more behavioral problems in children exposed to general anesthesia. An increased incidence of attention-deficit hyperactivity disorder has also been reported in anesthetic exposed children, particularly after multiple exposures. Summary: Nearly all clinical studies of anesthetic neurotoxicity are observational in nature, so the associations between anesthetic exposure and behavioral deficits cannot yet be directly attributed to the anesthetic medication. However, the finding of deficits in some neurodevelopmental domains and not others will help guide the selection of appropriate outcomes in future studies of anesthetic neurotoxicity that can further evaluate whether anesthetic medications have an impact on neurodevelopment in children.